Understanding the interplay of entrepreneurial orientation behaviors – does it hinder or facilitate creating new venture ideas by nascent entrepreneurial teams? - Monika Tkacz; Izaskun Agirre-Aramburu; Aitor Lizartza-Martín (Cogent Business & Management)
The research follows a current scientific stream in the literature on Entrepreneurial Orientation (EO) by studying team-level Entrepreneurial Orientation (TEO) behaviors in the context of nascent entrepreneurial teams (NETs). It aims to better comprehend the under-researched interplay of TEO behaviors of NETs during the venture concept creation stage. To this end, we have drawn on complexity science, ambidexterity and creativity theories, enabling us to understand the intricate dynamics between TEO behaviors that foster the exploration of novel ideas and the exploitation of high-quality business concepts. A sample of 88 NETs from the Mondragon Team Academy in the Basque Country was analyzed using PLS-SEM. The findings reveal both counterproductive and synergistic interactions, presenting unique insights into how NETs self-organize, manage tensions, and navigate uncertainty through TEO behaviors. By integrating theoretical discussion with practical implications, this study provides actionable guidelines to help entrepreneurial teams optimize behavioral tendencies, mitigate hindering effects, balance the trade-off between exploration and exploitation, and enhance NETs’ potential at the origins of entrepreneurship.